Reporting Bias and Monitoring in Clean Development Mechanism Projects* - Chen, Hui; Letmathe, Peter; Soderstrom, Naomi (Contemporary Accounting Research, 2021)
ABSTRACT The Clean Development Mechanism (CDM) is a flexible carbon market mechanism managed by the United Nations. The program grants tradable carbon emissions credits (Certified Emission Reductions) for carbon‐reducing projects in developing countries. A project can only be admitted to the program if it is not financially profitable, and thus would not take place without the emission credits granted through the CDM. In this paper, we examine how monitoring reduces incentives of companies to bias the reported expected financial viability of potential CDM projects to gain admission to the program. We find that reported rates of return, which are a key factor for admission to the program, tend to be downwardly biased and are negatively associated with the expected benefits stemming from forecasted greenhouse gas reductions. However, monitoring from various sources mitigates some of the distorted incentives and related reporting bias. Furthermore, the monitoring effect becomes much stronger after 2008, when the CDM Executive Board implemented a series of measures to strengthen the additionality testing that provides guidance for program applications.